2022
DOI: 10.3390/horticulturae8020114
|View full text |Cite
|
Sign up to set email alerts
|

High Light Intensity from Blue-Red LEDs Enhance Photosynthetic Performance, Plant Growth, and Optical Properties of Red Lettuce in Controlled Environment

Abstract: Plant factories using artificial light to produce vegetables have high energy costs due to the high demand for electricity for lighting. Compared to conventional light sources, light-emitting diodes (LEDs) offer the possibility of tailoring the light spectrum and regulating light intensity and are more energy-efficient in terms of energy conversion regardless of the levels of lighting intensity. Optimal light intensity and daily light integral (DLI) requirements are key factors for plant growth; however, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On exposure to green light, Pyropia haitanensis maintained the photochemical quenching and quantum yields of PSII but failed to maintain the electron transport efficiency as compared to the control. Moreover, exposure to blue-green light increased the photosynthetic pigments of different unicellular marine algae, and the changes in the quality of light significantly altered the composition of pigments in this organism [ 108 ]. A study conducted on Lactuca sativa showed the importance of green light intensity in plant photosynthetic performance [ 109 ].…”
Section: Quality Of Lightmentioning
confidence: 99%
“…On exposure to green light, Pyropia haitanensis maintained the photochemical quenching and quantum yields of PSII but failed to maintain the electron transport efficiency as compared to the control. Moreover, exposure to blue-green light increased the photosynthetic pigments of different unicellular marine algae, and the changes in the quality of light significantly altered the composition of pigments in this organism [ 108 ]. A study conducted on Lactuca sativa showed the importance of green light intensity in plant photosynthetic performance [ 109 ].…”
Section: Quality Of Lightmentioning
confidence: 99%
“…Cui et al 29 recommended a DLI of 6.35 mol m –2 day –1 for cucumber plug seedlings that could be achieved by using PPFD of 110–125 µmol m −2 s −1 and a photoperiod of 14–16 h. For indoor cultivation of red-leaf lettuce plants, a minimum DLI of 6.5 to 9.7 was suggested 35 . DLI requirement for lettuce ranges between 12 and 16 mol m –2 day –1 , however their value varies among species and cultivars 17 , 22 , 26 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The chlorophyll content decreased between the first and second cuts only in hydroponics, in which we observed as a response an increase in carotenoid content to cope with possible photodamage and nutrient imbalances, such as in iron or manganese [ 37 , 38 ]. It is well known that light and other environmental variables directly affect gas exchanges and plants’ capacity to absorb light [ 39 , 40 ]. In our experiment, the leading cause of reductions in gas exchange in both systems has to be ascribed to the different environment and the particular light scenario since the first cut occurred in July and the second in September, with a large difference in light intensity and daylight integrals being reduced in September.…”
Section: Discussionmentioning
confidence: 99%